Morphometric characterization and genetic distance in bitches (oryctolagus cuniculus) in several regions in Indonesia - Auliani Arafah; Abdul Razak (Tropical Genetics, 2022)
Rabbits are a group of animals that are very popular and enjoy doing the community. Rabbits in general have high biological and economic potential to produce quality meat, skin and hair, as well as pets (ornamental) and as modern business farming. Rabbits are well known to the people of Indonesia and developed mostly for rabbit farming. To obtain information about this, this study will discuss the objective of knowing the morphometric characteristics and genetic distances of rabbits. The parameters observed were head length, head width, ear length, ear width, chest circumference, chest width, chest width, humerus bone length, radius-ulna bone length, tibia bone length, and body length. The results of body variables measurement in FG rabbits had a higher mean for body size PK (12.64 cm), PTL (13.59 cm), LTL (6.47 cm), PH (9.52 cm), PRU (8, 95 cm) and PB (41.97 cm) for body size compared to other families. Genetic distance shows that it has a fairly close genetic distance (0.63106), while the farthest genetic distance is found in Rexb rabbits and ES rabbits, which is as far as 6.96749. Estimation of genetic distances and tree phenogram construction results from the estimation of kinship between other rabbit clumps.